2019
DOI: 10.1042/bsr20181931
|View full text |Cite|
|
Sign up to set email alerts
|

Modulation of miR-10a-mediated TGF-β1/Smads signaling affects atrial fibrillation-induced cardiac fibrosis and cardiac fibroblast proliferation

Abstract: Atrial fibrillation (AF) rat models and rat cardiac fibroblasts (CFs) with overexpressed or inhibited miR-10a were used to investigate the possible role of miR-10a-mediated transforming growth factor-β (TGF-β1)/Smads signaling in cardiac fibrosis and fibroblast proliferation in rats with AF. Gene ontology and pathway enrichment analyses were used to identify the possible function of miR-10a in cardiac fibrosis. The results showed that overexpressed miR-10a significantly prolonged the duration of AF, further el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…Co-regulates the transcription of target genes with other transcription factors [36]. Many articles indicate that repress the TGF-β1 channel can inhibit broblasts functions [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Co-regulates the transcription of target genes with other transcription factors [36]. Many articles indicate that repress the TGF-β1 channel can inhibit broblasts functions [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a powerful key fibrogenic cytokine. Many studies have confirmed that TGF-β1 plays an important regulatory role in cell proliferation, 11 differentiation, 12 migration, 13 immune regulation, 27 and extracellular matrix (ECM) transformation 28 in fibrotic diseases, and participates in tissue repair and fibrosis. The role of TGF-β1 in promoting fibrosis is mainly mediated by phosphorylating its downstream Smad proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TGF-β1 in promoting fibrosis is mainly mediated by phosphorylating its downstream Smad proteins. 11,14 TGF-β1/Smad signaling is identified as the main pathway of pulmonary fibrosis. The binding of TGF-β1 with its receptor II (TβRII) activates TGF-β1 receptor I (TβRI)'s kinase I. TβRI was phosphorylated and then phosphorylate Smad2 and Smad3, phosphorylated Smad2 and Smad3 afterwards bind to Smad 4 to constitute a Smad complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al [87] used AF rat models and rat cardiac fibroblasts with overexpressed or inhibited miR-10a to investigate the possible role of miR-10a mediated TGF-β1 in rats with AF. They found that downregulation of miR-10a inhibits collagen formation, reduces atrial structure remodeling and decreases proliferation of cardiac fibroblasts, which leads to the suppression of cardiac fibrosis in AF rats via inhibition of the TGF-β1 signaling pathway.…”
Section: Potential Of Mirnas As Treatment Of Afmentioning
confidence: 99%